2010
DOI: 10.1007/s00432-010-0908-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and comparison of mesenchymal stem-like cells from human gastric cancer and adjacent non-cancerous tissues

Abstract: Our findings suggest that MSC-like cells are components of the tumor microenvironment and provide proof for the origin of carcinoma-associated fibroblast, therefore may potentially be used as a target for gastric cancer diagnosis and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 19 publications
(25 reference statements)
1
70
0
Order By: Relevance
“…Although this concern has not, thus far, been borne out in human clinical trials, sub-populations of MSC-like cells have been found in the tumour microenvironment of several human cancers including gastric adenocarcinoma [103] and osteosarcoma [104]. Furthermore, some animal model studies have demonstrated preferential migration of intravenously administered MSCs to tumours [105,106].…”
Section: Tumorigenesis and Other Potential Adverse Effects Of Msc-evsmentioning
confidence: 96%
“…Although this concern has not, thus far, been borne out in human clinical trials, sub-populations of MSC-like cells have been found in the tumour microenvironment of several human cancers including gastric adenocarcinoma [103] and osteosarcoma [104]. Furthermore, some animal model studies have demonstrated preferential migration of intravenously administered MSCs to tumours [105,106].…”
Section: Tumorigenesis and Other Potential Adverse Effects Of Msc-evsmentioning
confidence: 96%
“…BM-MSCs were found to possess the property of spontaneous transformation [93], whereas the Hh pathway was recognized as the key factor for growth and proliferation of these spontaneously transformed MSCs in vivo [94]. MSC-like cells have been isolated from both human GC and adjacent noncancerous tissue [95].…”
Section: Hedgehog Pathwaymentioning
confidence: 99%
“…When bulk cancer cells are diminished by chemotherapy, CSCs are left in awkward situations without necessary nourishment, which may be sufficient for their extinction [133]. In addition, BMDCs and MSC-like cells recently isolated from GC and adjacent noncancerous tissues [95,136] may be the source of carcinoma-associated fibroblasts, which are suspected to promote tumor cell growth, and, along with MSCs, contribute to the CSC niche [137]. An in-depth understanding of in vitro/in vivo crosstalk between different cell types within the tumor milieu may give rise to improved anticancer strategies [137,138].…”
Section: Abc Transportersmentioning
confidence: 99%
“…MSC-like cells can be isolated from tumors such as bone sarcomas, lipomas, and gastric cancers [21][22][23][24] . The characteristics of these MSC-like cells, with respect to morphology, gene expression, surface antigen expression, and differentiation potential, are similar to those of BM-derived MSCs (BM-MSCs).…”
Section: Introductionmentioning
confidence: 99%